Byron and Shelley: Radical Incompatibles - Cochran, Peter (Romanticism on the Net, 2006)
AbstractMuch has been written about the relationship between these two poets, but few have wondered – how compatible were they in reality, when their poetry, ethics, philosophy of life, and even politics, were so radically different? In this new essay Peter Cochran tries to take an unsentimental view of how Byron and Shelley related, in both social and literary terms. What did each really think of the other? Were they friends to the end? Did Shelley borrow anything from Byron’s verse, or Byron from Shelley’s? Cochran looks at these questions, taking in en route the relationship between Alastor and Manfred, and – most controversially – Adonais and The Vision of Judgement. His conclusion is more disturbing than usual.